EMPLOYEE DISCIPLINE DEVELOPMENT STRATEGY (Study at the Head Office of Lhoksukon District, North Aceh Regency) - nurjamli jamli; Mai syuri (Universitas Malahayati, 2023)
According to Law No. 43 of 1999 in article 26 states that